The effect of sense of security on job performance of medical staff: the mediating effect of psychological capital - Xu, Yixuan; Zhan, Ningjing; Zhang, Dantong; Xie, Zhanghao; Li, Gege; Huang, Huigen (Frontiers in Psychology, 2024)
Objective: To investigate the current situation of sense of security, psychological capital and job performance of medical staff in Guangdong Province, and to explore the mediating role of psychological capital on the relationship between sense of security and job performance of medical staff. Methods:In this study, 969 health care workers were selected from February 2023 to April 2023 from 37 hospitals in Guangdong Province, China, using purposive sampling method. The Sense of Security Scale for Medical Staff(SSS-MS), psychological capital scale(PCS) in Chinese version and the Chinese version of job performance scale(JPS) were used in this study. We use SPSS 26.0 for statistical analysis and Amos 24.0 for structural equation modeling(SEM). The control variables entering SEM were selected by regression analysis. SEM analysis confirmed psychological capital scale's mediating function in the link between work performance scale and Sense of Security . Results: The overall SSS-MS, PCS, and JPS scores were 67.42±16.136, 87.06±15.04, and 77.87±10.50, respectively. The results of Pearson's correlation analysis showed that there was a positive relationship between PCS and JPS (r= 0.722, P < 0.01), SSS-MS and JPS (r= 0.312, P < 0.01), and SSS-MS and PCS (r= 0.424, P < 0.01). PCS demonstrated a fully mediating influence on the link between medical workers' SSS-MS and JPS, according to structural equation modeling. Conclusion: The JPS of medical personnel in Guangdong Province is at a medium level, with much room for improvement. PCS is positively impacted by a sense of security. There is a supportive correlation between PCS, JPS, and SSS-MS. Furthermore, PCS fully mediates the relationship between medical staff members' JPS and their SSS-MS. The Job Diamond-Resource model and Conservation of Resource theory are further validated and supplemented by the findings of this study, which also gives managers a theoretical foundation for enhancing medical staff performance.